Food practices as informing religious identity and connections in Oguta, Southeastern Nigeria. - Okwuosa, Lawrence N.; Okoli, Anuli B.; Ibenwa, Christopher N.; Iheanacho, Ambrose O.; Ezugwu, Joy (Food, Culture & Society, 2025)
There is an increasing awareness of African Traditional Religion and cultures in terms of identification, preservation, documentation and celebration mostly in the areas of festivals, masquerades, cultic groups, spirituality and architecture. However, one area that has not been explored is food practice. This daily human experience, which has aura of sacredness and moral values, is a significant part of African traditional religion. This study explores food practices in Oguta, Southeastern Nigeria with aid of ethnographic methods of observation and interview. The study finds that food practices in Oguta encapsulates the people's identity, religion, morality, and social connections and that if conscientiously done could add value to the recent consciousness. The findings provide new insights on food practices that can improve on human ecology in our 21st century world.